Awareness of eye donation among eye health workers (Journal of Patan Academy of Health Sciences, 2018)
Introductions: To assess the level of awareness and willingness of eye donation among eye health workers and compare it among the two institutes, one with cornea transplant services and other without cornea transplant services. Methods: This was comparative, questionnaire based, cross- sectional study under taken among eye health workers in two institutes. The questionnaire contained questions on demographic details, their awareness on eye donation, reasons for donating and not donating eyes by people as perceived by them, their intention to donate eyes and source of information. The responses were compared and statistically analyzed using chi-square test. Results: Of the 178 participants 132 participants were aware that eye donation was donation of eye after death. The most common source of information about eye donation was from eye professional. It was observed that 107 participants knew that eyes can be donated after death ideally within 6-8 hours of death. 139 respondents believed donated eye gives good sight to blind. Lack of awareness was cited as an important reason for people not donating eyes. Conclusions: Eye health workers are well aware about eye donation they can be actively involved in eye donation campaigns in community level and can act as counselors for eye donors.